Characterization of patients with hypertension in Santiago de Cuba - Raxsy Soler Santana; Marlenis Brossard Cisnero; Maribel Vaillant Rodríguez; Yalisle Omar Rodríguez; Mayelin Marin Mendez (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: Hypertension is a serious disorder that increases in a significant way the risk of suffering heart, brain, kydney diseases and others, at the same time that constitutes one of the main causes of early death in the world.  Objective: To characterize patients with  hypertension in  Santiago de Cuba. Method: A descriptive and cross-sectional study of 210 patients with hypertension, belonging to 30 family doctor´s offices of Santiago de Cuba, Contramaestre and San Luis municipalities of the mentioned county was carried out. The main variables analyzed were: age, sex, occupation, skin color, clinical course period of the disease, personal pathological history, nutritional evaluation, as well as control and treatment. Results: In the series the female sex, 65-79 age group, diabetes mellitus as personal pathological history prevailed, as well as overweight and obesity according to the nutritional evaluation. On the other hand, 57.1 % suffered from the disease for 10 years and 85.7 % had been indicated non pharmacological treatment; while 79.5 % didn't make physical exercises and just 50.5 % were classified as controlled.   Conclusions: The non control of blood pressure in the hypertensive population of this territory exposes them to the emergence of cardiovascular complications, with the repercussion that bears for the individual, family and society.